Uji toksisitas buah palem merah (Cyrtostachys renda Blume.) menggunakan metode brine shrimp lethality test (BSLT) method - Syamsurizal, Syamsurizal; Utami, Diah Tri; Sutrisno, Sutrisno; Efrini, Emi; Jumardi, Muhammad Ikhsan (Journal of Pharmaceutical and Sciences, 2023)
The red palm plant (Cyrtostachys renda) is a species of the Areca genus that grows widely in Jambi Province, making it an affordable plant to research for its medicinal properties. The Brine Shrimp Lethality Test (BSLT) is a toxicity test to screen for anticancer bioactive substances, with the test subject being Artemia salina Leach larvae, which are highly sensitive when exposed to toxic substances. The fruit and roots of C. renda were extracted using the maceration method by using a methanol solvent and partitioning using n-hexane, dichloromethane, ethyl acetate, and water. Based on the extract toxicity evaluation results, all extracts were toxic. Meanwhile, C.renda root dichloromethane extract had the highest toxic properties, with an LC50 value of 43.42 ± 0.659 ppm. However, the positive control's toxicity, potassium dichromate, was more toxic, with an LC50 value of 29.93 ± 0.668 ppm. The dichloromethane extract of C. renda roots can potentially be a poisonous agent. Further toxicity tests on cancer cells need to be carried out to be developed as an anticancer agent.